Recipient working status is independently associated with outcomes in heart and lung transplantation. Issue 2 (30th December 2018) - Rudasill, Sarah E.; Iyengar, Amit; Kwon, Oh Jin; Sanaiha, Yas; Dobaria, Vishal; Benharash, Peyman
Abstract: Employment status may capture elements of patients' physical strength, mental resilience, and socioeconomic status to better prognosticate transplant outcomes. This study characterized the effect of working status on thoracic transplant outcomes by evaluating the United Network for Organ Sharing registry for adult lung or heart transplants from 2005 to 2016. Kaplan‐Meier estimates illustrated 5‐year and 10‐year survival by working status at transplant, while multivariable Cox proportional hazards regressions controlled for baseline differences, including functional and socioeconomic status. Of 17 778 lung transplant recipients, 1700 (9.6%) worked at transplant and experienced significantly lower 5‐year mortality than nonworking recipients (38.6% vs 45.5%, P < 0.001). Of 21 394 heart transplant recipients, 1289 (6.0%) were employed and experienced significantly lower 10‐year mortality than nonworking recipients (34.1% vs 40.2%, P < 0.001). Adjusted Cox regressions demonstrated that employment significantly reduced mortality independent of functional status for both lung (HR: 0.86 [0.78‐0.95], P = 0.003) and heart (HR: 0.84 [0.72‐0.97], P = 0.023) recipients. After accounting for insurance status, the effect of working status persisted only in lung transplantation (HR: 0.89 [0.81‐0.98], P = 0.023). Since heart and lung transplant candidates employed at transplant face lower long‐term mortality, working status must encompass a broad set of physical, psychological, and socioeconomic variables that may prognosticate post‐transplant outcomes.